The Awareness of Speech and Language Therapy Among University Students - Aslı Altınsoy (Üniversite Araştırmaları Dergisi)
Although speech and language therapy has been improving in Türkiye since the early 2000s, there are few surveys of how much recognition of this profession has been achieved in the Turkish population. The first aim of this study was to determine the level of awareness of the speech and language therapy profession at Akdeniz University in Antalya. Secondary aims were to observe any differences when the students were evaluated in groups of health-related/non-health-related fields, and females/males. The study was conducted as a public awareness survey with 420 Akdeniz University students from 20 different faculties. Descriptive statistical analyses and Pearson Chi-squared test were performed. The results showed a low awareness of speech and language therapy profession in Akdeniz University students (n=124, 30%) and social media was the most common source of obtaining information. University students thought that speech and language therapists worked mostly in special education settings with children and adults who had speech sound disorders and stuttering. The recognition of speech and language therapy was greater among female students (x2 =7.665, p= .006) and students from medical majors (x2=13.219, p lt; .001). There is a clear need to raise awareness of speech and language therapy among university students in Antalya.